2016
DOI: 10.1159/000453143
|View full text |Cite
|
Sign up to set email alerts
|

The Vigabatrin Induced Retinal Toxicity is Associated with Photopic Exposure and Taurine Deficiency: An In Vivo Study

Abstract: Background/Aims: Retinal toxicity is one of the most commonly discussed and concerning adverse effects of vigabatrin (VGB). The present study explored the relationship between the VGB elicited retinal toxicity, photopic exposure, and taurine deficiency, aiming at screening for risk factors to minimize the adverse effects of VGB. Methods: The effects of VGB on function and morphology of mouse retinas were examined via a series of in vivo tests, including electroretinography (ERG), Spectral domain optical cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…49 The effect of this type of light on the retina and the intrinsic and extrinsic factors that may modify this response are at present not known, but it has been postulated that they may worsen retinal degenerations, especially in conditions of low plasma taurine levels, such as in vigabatrin-induced retinal toxicity. 4,10 In this study, rings devoid of cones were observed ALE both in control and in taurine-depleted animals mainly in an ''arciform'' area of degeneration located in the dorsal retina. In previous works, we have described this ''arciform area'' [18][19][20] as the area with maximal photoreceptor loss and vascular leakage of horseradish peroxidase immediately ALE.…”
Section: Taurine Depletion Increases Retinal Degenerationsupporting
confidence: 48%
See 3 more Smart Citations
“…49 The effect of this type of light on the retina and the intrinsic and extrinsic factors that may modify this response are at present not known, but it has been postulated that they may worsen retinal degenerations, especially in conditions of low plasma taurine levels, such as in vigabatrin-induced retinal toxicity. 4,10 In this study, rings devoid of cones were observed ALE both in control and in taurine-depleted animals mainly in an ''arciform'' area of degeneration located in the dorsal retina. In previous works, we have described this ''arciform area'' [18][19][20] as the area with maximal photoreceptor loss and vascular leakage of horseradish peroxidase immediately ALE.…”
Section: Taurine Depletion Increases Retinal Degenerationsupporting
confidence: 48%
“…This suggests that taurine supplementation may be beneficial to prevent retinal degenerations that proceed with photoreceptor or RGC loss and in which light may also be a critical etiologic factor, such as inherited retinal degeneration, AMD, or glaucoma. 10,22,95,96 Finally, our data also suggest that taurine supplementation may be beneficial to prevent retinal degenerations in which S-cone degeneration is the initial event, such as the photoreceptor degenerations that are initiated or worsened by light.…”
Section: Rgc and Iprgc Degeneration: Contributions From Light And/or mentioning
confidence: 55%
See 2 more Smart Citations
“…Taurine, as an endogenous antioxidant and a scavenger of the hydroxyl radical, may play a part in treating toxicity mediated by oxygen radical [23]. Many studies have demonstrated that Taurine has several pharmacological and biological properties including antioxidant, anti-fibrotic and elicited retinal toxicity [24, 25]. In addition, study has been reported taurine can be involved in male reproductive organs [26] and act as an antioxidant of sperm [27].…”
Section: Introductionmentioning
confidence: 99%